STORY TELLING IN TEACHING CHILDREN VALUES AND BUILD CHARACTER - Melvina Melvina (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
This paper intends to discuss about the advantages of storytelling toward children. Story telling teaches them values and build their character. The writing of the paper is based on the condition and some facts that happen nowadays where changes that occur in today’s society has led to a variety of positive and negative impacts. In positive side, the growth of knowledge, technology and information in the present time gives an ease in society life. However, negative impacts on society today such as violence/ bully, criminality, drug abuse, and free sex. All these caused by the decrease of values and moral in the society. To solve this problem, values and build character is highly needed. In this case, through story telling not only will teach children values and build their character but also the effective way to introduce them about culture and moral to the children. Key words: build character, storytelling, value.